Comprehensive Perception Approach of Adoption: Innovative Wrap & Plant Technology for Nematodes Management on Yam - Dedehouanou, Houinsou; Affokpon, Antoine (Advances in Social Sciences Research Journal, 2022)
ABSTRACT A new agricultural practice, wrap & plant technology, was experimented in yam fields on three different sites in the centre-north of Benin. These sites were "Savalou", site 1, "Savè", site 2 and “Glazoué”, site 3. The research sought to highlight the perception of various actors from the vegetative to the culinary phases. Two improved practices were introduced: treatment A (wrapping of seed yam cv. Klatchi with banana-fibre paper, impregnated with micro-doses of abamectin), treatment B (wrapping of seed yam of cv. Klatchi using banana-fibre paper alone). On the basis of a Comparative Appraisal Index (CBI), that is, the practice introduced was well appreciated by enumerators if the difference in perception scores of characteristics was greater than zero. In terms of results, treatment A seemed to be the most popular practice on sites 1 and 2. On site 3, treatment B seemed to substitute for A. While in the first two sites, the sensory characteristics of dishes and the agro-morphological descriptors constituted a main component of favourable perception, the descriptors from agro-morphological and harvest phases were very much important at site 3. In terms of the decision to adopt a treatment, it depended significantly amongst other socioeconomic characteristics of the respondents on the sex, number of years of experience, membership in an association, level of education, other income generating activity and the site. For future expansion of introduced practices, agricultural research needs to address socioeconomic characteristics and to improve agro-morphological descriptors. Key-words: Abamectin, actors, Dioscorea spp., nematode management, sensory selectivity, Benin